Measurement Accuracy of Freezing of Gait Scoring Based on Videos - Kondo, Yuki; Mizuno, Katsuhiro; Bando, Kyota; Suzuki, Ippei; Nakamura, Takuya; Hashide, Shusei; Kadone, Hideki; Suzuki, Kenji (Frontiers in Human Neuroscience, 2022)
Freezing of gait (FOG) is a common symptom in the late stages of Parkinson’s disease and related disorders. Videos are the gold standard method to conduct FOG scoring; however, the measurement accuracy of FOG scoring based on videos has not been formally assessed, despite its use in previous studies. This study aimed to calculate the measurement accuracy of video-based FOG scoring. Three evaluators scored the FOG based on 157 video data points collected from 21 patients using an annotation tool. One evaluator measured the intra-rater reliability of the retest. The total duration of observed FOG, percentage of the time spent with FOG during the walking task (%FOG), and FOG phenotypes (shuffling, trembling, and complete akinesia) were evaluated. Intraclass correlation coefficients were used to determine the intra- and inter-rater reliabilities. The duration of FOG and %FOG showed good measurement accuracy for both intra-rater and inter-rater reliabilities. However, the FOG phenotypes showed poor measurement accuracy in inter-rater reliability. These results indicate that the temporal characteristics of FOG can be scored with a high degree of measurement accuracy, even with different evaluators; conversely, the FOG phenotypes need to be scored by several evaluators.